Algorithm as a problem solving technique for teaching and learning of the Malay language - Nazir, Faridah; Jano, Zanariah; Omar, Norliza (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
The aim of the study was to determine the effectiveness of using scratch program to teach Malay language subject. 32, 4th year students in a primary school of Seremban district participated in the study. A case study was used. The teachers teach Malay subjects using scratch programs with the theme of agriculture and title of food product from agriculture. The students were to arrange the basic words into grammatical sentences based on the scratch program and write a cake recipe using an algorithmic technique, a series of instructions contained in the scratch program. This conceptual teaching and learning algorithm was conducted in five steps namely the induction set; step 1; step 2; step 3; and enrichment and recovery. Students could understand the concepts of algorithms taught and did not require recovery activities. This implies that the algorithm concept of how to prepare a cake through a scratch program has been fully understood by the students. Students are also excited about the algorithmic techniques and the scratch program generated. They remain focused throughout the session which shows that the use of algorithms and scratch programs is better than conventional methods in teaching the Malay Language.